Environmental education research in Brazil - Thiemann, Flávia Torreão (2018)
This Editorial to the current collection provides a brief historical, cultural, regional and contemporary picture of environmental education research in Brazil. Its main purpose is to offer readers a short background and orientation to the collection, and in so doing, illustrate how its contributions relate to some wider tendencies, trends and issues in environmental education, as well as to different locales of research and knowledge generation in the country. Of particular note for environmental education in Brazil are: the effects of social and political backdrops and issues, the unique environments on which environmental education is grounded, and how environmental education research, in turn, may echo or influence particular educational and public policies.